Kinerja Kerbau Betina di Pulau MOA, Maluku (The Productivity of Female Buffaloes at MOA Island, Maluku) - Justinus Pipiana; Endang Baliarti; I Gede Suparta Budisatria (Buletin Peternakan, 2010)
The objectives of the study was to identify the existence, productivity, reproductive performances and its relation on the reproductive efficiency, body measurements and weight of female buffalo at Moa island, Maluku Barat Dayaregency, Maluku province. There were 96 farmers used as respondents, 222 female buffaloes and secondary data from Agricultural Department in that area that were observed. Survey method and descriptive analysis were applied tocollect all of information required. Body measurement was accompleted by direct measurement on the body, consisted of body length, withers height, chest depth, heart girth, rump height, rump width, and ages of buffaloes evaluated. Theresults showed that reproduction efficiency (RE) was 70.91±10.84%. Body measurements and weight of female buffaloes at 2-3 year old were body length 88.92±9.94 cm; heart girth 136.69±21.05 cm; withers height 94.77±7.23 cm;rump height 44.77±5.54 cm; and body weight 192.46±29.12 kg. At 3-4 years old of female buffaloes, the body length, heart girth, withers height, rump height, chest depth, rump width and body weight were 106,21±4,19 cm; 163.61±16.40cm; 110.03±6.14 cm; 109.08±5.88 cm; 65.58±6.69 cm; 46.82±4.62 cm; and 253.45±30.79 kg, respectively. At 4-5 year old, the body length, heart girth, withers height, rump height, chest depth, rump width, and body weight of females buffaloes were 116.14±10.98 cm; 174.04±12.12 cm; 115.07±3.23 cm; 113.07±3.74 cm; 67.36±7.44 cm; 48.07±3.74 cm; and 270,42±27,24 kg, respectively, while for female buffaloes of more than 5 year old, were 121.44±12.22 cm; 180.01±16.63 cm; 120.19±3.76; 119.49±13.74 cm; 79.40±5.52 cm; 58.72±4.88 cm; and 292.09±29.76 kg. It was concluded that productivity of female buffaloes at Moa island have not optimalet, but it has good performances which can be further developed.(Key words: Productivity, Female Buffaloes, Moa Island)